“Italy, for Example, Is Just Incredibly Stupid Now”. European Crisis Narrations in Relation to Italy's Response to COVID-19 - Viola, Lorella (Frontiers in Communication, 2022)
Crisis narratives shape public understanding and, consequently, the response to the crisis itself. In the context of the COVID-19 pandemic, when in February 2020 Italy was experiencing more cases than any other country, the Italian response to the crisis originated debates over how to best respond to the outbreak. Informed by Critical Discourse Analysis theory (Fairclough & Wodak 1997) and using narrative networks (Bearman & Stovel, 2000; Gimenez, 2010) as a framework for the critical analysis of narratives, this study analyzes the discourse strategies employed by experts, politicians and other social actors from Spain, France, the Netherlands, and the UK when presenting their domestic measures in relation to Italy’s response to coronavirus. The analysis shows that less drastic handlings of the pandemic were connected to country-specific shared experiences, such as a sense of national exceptionalism. At the same time, however, they were tied to a number of negative stereotypes which at times referred to the cultural traits of Italians (e.g., disorganized, lazy, undisciplined), at times to their healthcare system (i.e., backward hospitals), and other times resulted in inappropriate communication styles (i.e., supposed Italians’ stupidity, lack of hygiene). This article presents a comprehensive ‘timeline of narratives’ which opens avenues for a critical reflection on the impact such narratives may have had on the understanding of the crisis, including the creation of a negative climate of division.